Synthesis of Visible Light Active CuFe2O4/g-C3N4 Photocatalyst for Water Splitting - Maruthamani, D.; Vadivel, S.; Kumaravel, M. (University of Jaffna, 2019)
A facile g-C3N4 supported CuFe2O4 composite photocatalyst has been prepared by a simplistic onepot calcination approach using urea and a CuFe2O4 gel as precursors. The compounds obtained were analysed with Raman Spectroscopy, X-Ray Diffraction (XRD), X-Ray Photoelectron Spectroscopy (XPS), Scanning Electron Microscopy(SEM) and Energy Dispersive Spectroscopy (EDS) in order to obtain their morphological and structural properties. Optical behaviour was studied by UV–vis Spectroscopy. In this composite, CuFe2O4 was finely dispersed in g-C3N4 matrix, resulting in much improved efficiency of CuFe2O4/g-C3N4 heterojunction in photocatalytic H2 production by water splitting under visible light. The peak 104 μmol h−1 was obtained at optimized loading amount of 3% CuFe2O4 in the composites, which was about 4 times of that on the pure g-C3N4 obtained from urea. This remarkable improvement can be attributed to the enhanced visible light absorbance, improved surface area and charge carrier separation and transfer ability.